Effects of Sport Teaching on Students' Enjoyment and Fun: A Systematic Review and Meta-Analysis - Rodríguez Macías, Manuel; Abad Robles, Manuel Tomás; Giménez Fuentes-Guerra, Francisco Javier (Frontiers in Psychology, 2021)
The methodology used in the sport teaching influences not only the technical and tactical learning, but also psychological and social dimensions such as enjoyment. The aim of this study was therefore to conduct a systematic review and meta-analysis of the effects of interventions using conventional and non-conventional sport teaching methodology on students' enjoyment/fun. The search was carried out following the PRISMA Statement, in the databases of Web of Science, PubMed, Scopus, SportDiscus, Eric and PsycInfo. A total of 8 articles were considered to meet the inclusion criteria. The meta-analysis yielded a moderate effect size of 0.65, and a 95% CI from 0.40 to 0.90 in favour of non-conventional teaching methods, although no non-conventional approach was found remarkable, as several models showed significant differences. Nevertheless, the heterogeneity of the interventions was large and the quality of the evidence, according to GRADE, was very low. In conclusion, the use of non-conventional models in sport teaching with the aim of increasing the enjoyment/fun of boys and girls is advised. These suggestions could be useful for teachers and sport coaches in order to increase the enjoyment/fun of their trainees during sport practice.